Pengaruh Rasio Likuiditas, Struktur Modal Dan Rasio Aktivitas Terhadap Profitabilitas Pada PT Alakasa Industrindo Tbk Periode 2014 - 2023 - Sri Ayu Prihatini; Muhamad Nurhamdi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effect of liquidity ratio, capital structure, and activity ratio on profitability at PT. Alakasa Industrindo, Tbk during the period 2014–2023. Profitability in this research is proxied by Return on Assets (ROA), while the liquidity ratio is represented by the Current Ratio (CR), capital structure by Debt to Equity Ratio (DER), and activity ratio by Total Asset Turnover (TATO). This research uses a quantitative approach with multiple linear regression analysis. The data used are secondary data obtained from the company’s annual financial reports during the observation period. The results show that partially, CR and TATO have a significant effect on ROA, while DER does not have a significant effect on ROA. Simultaneously, the three independent variables have a significant effect on ROA. Based on the findings, the company is advised to optimize the use of current assets and operational efficiency to generate profits, while maintaining a balanced capital structure to sustain and improve profitability in the future.